2011
DOI: 10.1179/026708309x12560332736593
|View full text |Cite
|
Sign up to set email alerts
|

On preventing HAZ cracking in laser welded DS Rene 80 superalloy

Abstract: The heat affected zone (HAZ) cracking behaviour in a laser beam directionally solidified (DS) Rene 80 nickel based superalloy subjected to preweld heat treatments was studied. The HAZ cracks in the alloy are grain boundary liquation cracks caused by liquation reaction of both non-equilibrium secondary solidification product, MC carbides and equilibrium solid state reaction product, γ′ precipitates. In contrast to theoretical prediction based a preweld heat treatment that reduced grain boundary liquid film thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…According to relevant research, the HAZ liquation cracking has a great relationship with the width and grain size of HAZ. The HAZ liquation cracking was easy to occur in many nickel-based alloys during welding [20][21][22]. Idowu [23] showed a significant relationship between liquation cracking and grain size.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
“…According to relevant research, the HAZ liquation cracking has a great relationship with the width and grain size of HAZ. The HAZ liquation cracking was easy to occur in many nickel-based alloys during welding [20][21][22]. Idowu [23] showed a significant relationship between liquation cracking and grain size.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
“…Larger grain sizes in EQ alloys are beneficial from a creep strength perspective due to the reduction of overall grain boundary area. Under rapid heating, the grain boundary phases are unable to dissolve fully into the surrounding matrix and their partial dissolution leads to the formation of a low melting point eutectic and melting of the grain boundary region . Rush et al showed that an increase in the grain size lowers the ductility and causes more segregation of melting point depressing elements at the grain boundary, resulting in an increase in average crack length in the cold metal transfer process, where material was welded in the solutionized state.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that laser treatment resulted in different hot crack lengths in the heat‐affected zone, which depended on local microstructural configuration in the close region of the treated region. The prevention of heat‐affected zone cracking in laser‐treated nickel‐based superalloy was examined by Osoba et al . They demonstrated that application of a pre‐weld heat treatment prevented the formation of the intergranular borides while resulting in a nearly crack free heat‐affected zone in the laser‐treated layer.…”
Section: Introductionmentioning
confidence: 99%
“…Hot cracking in the heat-affected zone of laser-treated nickel-based superalloy was investigated by Matijasevic-Lux et al [13] They showed that laser treatment resulted in different hot crack lengths in the heat-affected zone, which depended on local microstructural configuration in the close region of the treated region. The prevention of heat-affected zone cracking in laser-treated nickel-based superalloy was examined by Osoba et al [14] They demonstrated that application of a pre-weld heat treatment prevented the formation of the intergranular borides while resulting in a nearly crack free heat-affected zone in the laser-treated layer. The age-hardening mechanism of nickelbased superalloy subjected to a laser rapid forming was studied by Xiaoming et al [15] They indicated that tensile strength after the laser treatment process increased considerably as compared to the strength of untreated workpiece.…”
Section: Introductionmentioning
confidence: 99%